Two interesting cases of EEC syndrome - Mariyam Iqbal Ali; K. Aravinda; Nitin Kumar Nigam; Iqbal Ali (Journal of Oral Biology and Craniofacial Research)
Aim: To report two cases of EEC syndrome with oral involvement to highlight the fact that the dental surgeon may be among the first to recognise the condition. Introduction: The EEC syndrome, a rare congenital syndrome is characterised by ectodermal dysplasia, distal limb anomaly, cleft lip and palate and lachrymal duct anomalies although the term oligosymptomatic EEC syndrome has been suggested for cases in which ectrodactyly may be absent and that such cases should not be deprived of the EEC syndrome diagnosis. It is usually inherited as an autosomal dominant trait with variable expressivity and penetrance and all these features rarely coexist in a single individual. Conclusion: Both our cases had all three characteristic features of the EEC syndrome. Other syndromes with overlapping features such as the Rapp–Hodgkin syndrome and the AEC syndrome should be considered in the differential diagnosis of incomplete forms of EEC syndrome. Clinical significance: It is important to follow an interdisciplinary approach to attain the greatest degree of success possible in the treatment of such cases.